Built in, not bolted on: responsible innovation in UK CDTs - the new normal? - Ten Holter, C; Stahl, B; Jirotka, M (Emerald, 2022)
Purpose The purpose of the study detailed here was to engage with Directors of Centres for Doctoral Training (CDTs) during the first year of their new Centres to form a snapshot view of the nature and type of training that was being incorporated and how this might affect the wider institution – in this case the university. Using an organisational learning lens, this paper empirically examines the work-in-progress of the responsible innovation (RI) training in CDTs to assess how new RI understandings are being created, retained and transferred within the CDTs, questioning whether this process represents a programme of “institutionalisation”.